Evaluación agronómica de Cratylia argentea en México y Centroamérica - Argel M., Pedro J. (International Center for Tropical Agriculture, 1996)
The shrub Cratylia argentea is native from Brazil, Peru and Bolivia. It does not have more than a decade that it was introduced for evaluation to Mexico and Centro América region. Preliminary reports indicate that this shrub adapts better to well drained savanna and humid and subhumid ecosystems with moderately fertile soils. The more advanced accession regionally is C. argentea CIAT 18516. Reported yields of edible dry matter (EDM) are variable-from a mean of 8 g/EDM/plant/cut in Isla, Mexico, every 4 weeks, up to 123 g/EDM/plant/cut every 8 to 14 weeks in Atenas, Costa Rica. Differences are due to site effects but also to cutting height and plant density variations. Cratylia argentea shows good regrowth after cutting, particularly during prolonged dry periods (5 or more dry months). EDM during this period range between 30 percent to 40 percent of the total produced annually for different accessions. This shrub flowers and set seed of good quality, but there are not reported studies aimed at crop management for seed production. Research is also needed on animal production, plant density, height and frequency of cutting, plant age at first cut, response to soil nutrients and to the inoculation with Rhizobium